The Effects of Hyperbaric Oxygen Therapy on Blood Glucose Levels and Lipid Profile in Diabetes Mellitus Patients - Andika Aliviameita; Nevy Elensya; Puspitasari Puspitasari; Sri Mukhodim Faridah Hanum (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Diabetes mellitus and its complications are still a major health problem in the world. Diabetes mellitus is closely related to the lipid profile, especially concerning the cardiovascular disease. A method that can be used to treat diabetes mellitus is hyperbaric oxygen therapy (HBOT). This study aims to observe changes in blood glucose levels and lipid profiles in patients with diabetes mellitus with hyperbaric oxygen therapy. The determination of blood glucose levels and lipid profiles is done by photometry. A total of 30 patients with diabetes mellitus examined for their blood glucose level and lipid profile before and after hyperbaric oxygen therapy. In the Paired T-test, there were significant decrease in blood glucose levels (p= 0,000), total cholesterol (p= 0,000), and triglycerides (p= 0,000) after hyperbaric oxygen therapy. The conclusion of this study shows there is a significant decrease in blood glucose level and lipid profile (total cholesterol, and triglycerides) after hyperbaric oxygen therapy.